2011
DOI: 10.3102/0002831210374874
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Inaccuracy in Teachers’ Perceptions of Young Children’s Cognitive Abilities

Abstract: Teachers' subjective understandings of their students' cognitive abilities have important implications for classroom interactions, children's access to resources and opportunities, and educational equity more broadly. Using nationally representative data and three-level hierarchical linear models, this study explored the links between teacher perceptions and children's sociodemographic backgrounds. The authors find that teachers perceive substantial racial-ethnic, socioeconomic, and gender differences in child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
282
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(306 citation statements)
references
References 40 publications
(52 reference statements)
12
282
6
6
Order By: Relevance
“…There may be two explanations for these results. First, the well-documented difference in teacher expectations between boys and girls (e.g., de Boer et al 2010, Ready andWright 2011;Rubie-Davies 2008;Timmermans et al 2015) is only a partly true gender bias, but stems from differences between boys and girls in actual behavior that is reflected in the teachers' perceptions of student attributes. Second, it may still be ''gender bias'' if teachers base their expectations of boys and girls on how they perceive them to behave rather than on their actual behavior in the classroom.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There may be two explanations for these results. First, the well-documented difference in teacher expectations between boys and girls (e.g., de Boer et al 2010, Ready andWright 2011;Rubie-Davies 2008;Timmermans et al 2015) is only a partly true gender bias, but stems from differences between boys and girls in actual behavior that is reflected in the teachers' perceptions of student attributes. Second, it may still be ''gender bias'' if teachers base their expectations of boys and girls on how they perceive them to behave rather than on their actual behavior in the classroom.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…All in all, the current findings add to the literature not only by providing evidence on the relationship between teacher expectations and perceptions of student behavior (Bennet et al 1993;Hecht and Greenfield 2002), but also by showing that this association is rather complex due to differences among teachers and dependence on students' performance levels. Further investigation of the association between perceptions and expectations may be needed, as perceptions and expectations may sometimes be inaccurate (Lane et al 2006;MacLure et al 2012) and both may influence teacher behavior and the subsequent performance of students (e.g., Bennet et al 1993;Brophy and Good 1970;Hamre and Pianta 2006;Ready and Wright 2011;Rubie-Davies 2007, 2008, 2010.…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that teachers' perceptions, appreciations and expectations concerning students' academic aptitude may have implications for their teaching practices by influencing, on the one hand, the way they select teaching strategies and evaluate students and, on the other, by influencing students' self-evaluations and perceptions about their abilities (Alvidrez & Weinstein, 1999;Ready & Wright, 2011;Südkamp, Kaiser, & Möller, 2012).For instance, according to their expectations, teachers may present different patterns of interaction with students, including the use of nonverbal cues or positive reinforcement (Babad, 1993;Kuklinski & Weinstein, 2000;Rubie-Davies, Hattie, & Hamilton, 2006). The concretization of teacher expectations on students' achievement can be of an indirect or direct nature (Kuklinski & Weinstein, 2000).The latter can arise from differences in the curriculum exposure, that is, students may perform differently because they are given distinct opportunities for knowledge acquisition and achievement of skills.…”
Section: Teacher Expectations and Students' Academic Achievementmentioning
confidence: 99%
“…In the U.S., teachers commonly see students who are White and Asian as more teachable than students who are Black and Latino, and students of middle-or upper-class backgrounds as more teachable than those from lower-class backgrounds. Teachers justify their expectations on the basis of student behavior (Minor, 2014), family background, and community context, particularly teachers' beliefs about the extent to which parents value education (Gay, 2010;Hauser-Cram, Sirin, & Stipek, 2003;Lynn, Bacon, Totton, Bridges, & Jennings, 2010;Ready & Wright, 2011;Warren, 2002).…”
mentioning
confidence: 99%